Tra la volontà di potenza e la volontà di libertà: lo spazio del pensare francescano - Todisco, Orlando (Miscellanea francescana, 2020)
There are two perspectives within which history has always moved: the perspective of domination and the perspective of service, or even the will to power and the will to freedom or, more radically, being as self-affirmation and being as donation. It is the swaying movement of history. The line that, so far, has been imposed is the will to power as a right-to-be, a source of vindication. Being and power-of-being are one. If this is the winning line, the Franciscan proposal overturns the structure passing from self-affirmation to self-giving of being, or similarly, and in an abbreviated form, passing from being as a right-to-being to being as a gift-of-to be. We are beyond the Greek horizon, for instance, beyond the horizon of that thinking that excludes the creative act. It is the horizon of meaning. This horizon, absent from the philosophical proposals that disregard the divine creative act, for which the world is its meaning, because it is there, created by no one and no one cared for; in the Franciscan perspective it imposes itself with arrogance, because it moves from presupposition that what is refers to a being who has chosen and realised what he could not choose and not realize. The question becomes consequent: why did he do what he could not do? The problem of meaning will become central to both modern and contemporary philosophy, but faced with improper tools, because both philosophical lines are independent of the divine creative act and therefore do not place at the centre the figure of gift and service, but that of law and of possession. The Franciscan proposal wants the problem of meaning to be faced in the light of the transcendence of the will of freedom of the oblative sign, to be placed as the sole apriori.